2015
DOI: 10.1007/s00468-015-1275-3
|View full text |Cite
|
Sign up to set email alerts
|

Histology of Quercus ilex roots during infection by Phytophthora cinnamomi

Abstract: Key message The speed of infection of Quercus ilex by Phytophthora cinnamomi is influenced by the method of inoculation used, and structural changes in the host do not differ depending on whether primary or secondary roots are infected. Abstract This study aimed to elucidate the infection process of the invasive pathogen Phytophthora cinnamomi on primary and secondary roots of 2-month-old Quercus ilex seedlings. To test if different methods of inoculation lead to different changes in the host caused by the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
(100 reference statements)
1
29
0
Order By: Relevance
“…mRNA expression from genes for tannin biosynthesis was analyzed by qPCR on nucleic acids isolated after treatments by P. cinnamomi infection and/or defoliation of Q. ilex . Sampling was performed 4 days post infection, corresponding to a late stage during the biotrophic growth of the oomycete (Redondo et al ), whereas gene expression was studied in leaves, the tissue where interactions between herbivory and P. cinnamomi infection are expected to take place. Leaves of Q. ilex accumulated detectable amounts of ANR , ANS , LAR1 , SDH1 and SDH2 (but not LAR2 ) transcripts (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA expression from genes for tannin biosynthesis was analyzed by qPCR on nucleic acids isolated after treatments by P. cinnamomi infection and/or defoliation of Q. ilex . Sampling was performed 4 days post infection, corresponding to a late stage during the biotrophic growth of the oomycete (Redondo et al ), whereas gene expression was studied in leaves, the tissue where interactions between herbivory and P. cinnamomi infection are expected to take place. Leaves of Q. ilex accumulated detectable amounts of ANR , ANS , LAR1 , SDH1 and SDH2 (but not LAR2 ) transcripts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…*P < 0.05 and **P < 0.01. treatments by P. cinnamomi infection and/or defoliation of Q. ilex. Sampling was performed 4 days post infection, corresponding to a late stage during the biotrophic growth of the oomycete (Redondo et al 2015), whereas Fig. 4.…”
Section: Signaling Of Biotic Stress On Gene Expression For Tannin Biomentioning
confidence: 99%
“…Causes of differential survival of seedlings depending on the Phytophthora species have not been described in Q. ilex . Variation in seedling mortality may have resulted from variation in growth of Phytophthora hyphae in host tissue (Redondo et al ., ), root necrosis, lack of water absorption capacity of infected plants following root destruction (Sghaier‐Hammami et al ., ), hormonal changes triggering a generalized dysfunction in plant water relations, or involvement of toxic metabolites (Jung et al ., ; Osswald et al ., ). In the present study, the longest tap roots and highest necrosis lengths were observed in seedlings growing in P. gonapodyides ‐infested soils.…”
Section: Discussionmentioning
confidence: 99%
“…Because seed weight affects early‐life traits of plants such as growth and resistance to pathogens (Solla et al ., ; Vivas et al ., ), this study included a morphological approach using seed weight and seed asymmetry as covariates of plant mortality. Moreover, because fine roots are important elements of plant health (Redondo et al ., ), and species of the genus Phytophthora are among the organisms that most seriously damage roots, plant performance was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Although previously considered to be a necrotrophic pathogen, recent observations of putative P. cinnamomi haustoria within cortical and vascular tissues in a number of host plants, including Lupinus augustifolius (Fig. 5A), have suggested that P. cinnamomi can grow as a hemibiotroph (Crone et al, 2013b;Redondo et al, 2015). In Arabidopsis, the extrahaustorial membrane surrounding haustoria of the Oomycete, Hyaloperonospora arabidopsidis, contains the plasmodesmata-located protein1 (PDL1) (Caillaud et al, 2014).…”
Section: Hyphal Growthmentioning
confidence: 99%